Case study: technical approaches to the water use efficiency indicators and socioeconomic and policy constraints to their operative use in Morocco - Dahan R. (WEMED workshop: how to advance the knowledge on water use efficiency in the Mediterranean region ?, 2007)
With growing population, water scarcity and increasing competition across water-using sectors, the need for water savings and improvement in water use efficiency has increased in importance in water resources management. In Morocco and in the Mediterranean region in general, water is the major factor limiting agricultural development under both rain-fed and irrigated conditions. This paper is a case study of Morocco with regard to water use efficiency indicators. It analyses the water resources, their mobilization, affectation and evolution; the climate context characterized by erratic and unpredictable rainfall amount and distribution both inter and intra-annually; the technical approaches developed to improve water use efficiency, mainly proven soil and crop management practices; and the socio-economical factors limiting water use efficiency practical use. The challenges to improve water use efficiency in agriculture reside on the conjunctive intervention at policy, community, technology and management levels. Based on Moroccan case study and available scientific and technical information in the region, future needs and prospects on water use efficiency improvement are discussed.
Workshop on: How to Advance the Knowledge on Water Use Efficiency in the Mediterranean Region ? 2006/10/26-28, Valenzano (Italy)